On a bounded almost periodic solution of a semilinear parabolic equation - Assanova, A. T. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain sufficient conditions for the existence and uniqueness of a bounded almost periodic solution of a semilinear parabolic equation.